Durum wheat Teosinte Branched1 null mutations increase tillering. Issue 4 (17th June 2022) - Volkman, McKenna M.; Martin, John M.; Hogg, Andrew C.; Wright, Lucas; Hale, Caleb; Carr, Patrick M.; Giroux, Michael J.
Abstract: Wheat ( Triticum spp.) yield is increased by either producing and testing variants of yield‐limiting genes or crossing to create new allelic combinations. Tiller number and seeds per tiller influence wheat yield, and both are impacted by the Teosinte Branched1 ( TB1 ) gene. We screened 16 hard red spring wheat ( Triticum aestivum L.) cultivars, 15 hard red winter wheat cultivars and lines, and 10 durum wheat [ Triticum turgidum L. subsp. durum (Desf.) van Slageren] cultivars and lines commonly grown in Montana and found several previously reported TB1 missense alleles along with one new silent and a missense TB1‐A1 allele among the 16 hard red spring wheat cultivars but no TB1 null alleles. Among the 10 durum cultivars, five carried a TB1‐B1‐S184G missense allele and all winter wheat cultivars carried wild‐type TB1 alleles. To determine the impact of TB1 null alleles, this study examined durum wheat genotypes varying for TB1 null alleles created by ethyl methanesulfonate (EMS) mutagenesis. The goal was to determine the impact of TB1 null alleles on tillering, agronomic, and seed traits. The impact of TB1 null alleles was studied alone and together in field trials. The TB1 single‐ and double‐null mutants produced up to 15% more tillers and 18% with positive trends toward increased plant biomass. The results of this research demonstrate that the integration of EMS‐derived TB1 null alleles may prove useful in increasing small‐grain tillering to optimize plant biomass and yield under different growing conditions. Core Ideas: Teosinte Branched1 null alleles increase wheat tillering. Selection for increased tillering can increase wheat biomass. Teosinte Branched1 null impact is influenced by the environment.